Excessive daytime sleepiness and nocturia in women - Sacomori C.* (2014)
Objective: To investigate associations between excessive daytime sleepiness and nocturia in women. Method: A total of 488 women aged 18-89. years who underwent screening for cervical cancer at one institution in Florianópolis, Brazil, took part in this investigation. Sleep issues and daytime sleepiness, urinary frequency, and nutritional status were investigated. Results: The prevalence of excessive daytime sleepiness was 31.3%. Most of the women reported having nocturia, since 32.4% reported one nocturnal voiding, and 24.3% two or more nocturnal voidings. Higher nocturnal voiding frequency was identified in women who spent longer in bed (P= 0.028) and had worse quality of sleep (P<. 0.001), higher daytime sleepiness (P= 0.016) and excess body weight (P<. 0.001). A higher prevalence of daytime sleepiness was also observed in those women assumed to have urine leakage (P= 0.006). Women with two or more nocturnal voidings presented 1.58 (CI: 1.06-2.37) higher prevalence of daytime sleepiness independent of time in bed (P= 0.030). Conclusion: Women with at least two nocturnal voidings presented higher prevalence of daytime sleepiness, worse sleep quality, and longer time in bed. Moreover, women with daytime sleepiness presented higher frequency of urine leakage. © 2014 Elsevier B.V.